Acyl hydrolases from trans-AT polyketide synthases target acetyl units on acyl carrier proteins. Issue 30 (22nd March 2016) - Jenner, Matthew; Afonso, Jose P.; Kohlhaas, Christoph; Karbaum, Petra; Frank, Sarah; Piel, Jörn; Oldham, Neil J.
Abstract : Acyl hydrolase (AH) domains are a common feature of trans -AT PKSs, perform a proofreading function by removing principally acetyl chains from stalled sites. Abstract : Acyl hydrolase (AH) domains are a common feature of trans -AT PKSs. They have been hypothesised to perform a proofreading function by removing acyl chains from stalled sites. This study determines the substrate tolerance of the AH PedC for a range of acyl-ACPs. Clear preference towards short, linear acyl-ACPs is shown, with acetyl-ACP the best substrate. These results imply a more targeted housekeeping role for PedC: namely the removal of unwanted acetyl groups from ACP domains caused by erroneous transfer of acetyl-CoA, or possibly by decarboxylation of malonyl-ACP.